Functional Movement Screen™ and history of injury in the assessment of potential risk of injury among team handball players - Slodownik, R.; Ogonowska-Slodownik, A.; Morgulec-Adamowicz, N. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Handball is known to be one of the team sports representing the highest risk of injury. Several investigators have tried to identify injury risk factors in team sports including handball and suggested the need to develop an optimal tool to capture and quantify the potential risk of injury. The aim of the study was to evaluate potential risk of injury among handball players. METHODS: This was a mixed-design study. Handball players from 1st and 2nd division were evaluated (N.=30) using the Functional Movement Screen™ (FMS™). Additionally, self-reported history of injury was collected during FMS™ evaluation and after 6 months. Competitive level, training experience, playing position, anthropometric features, symmetry of movement patterns and history of previous injury were analyzed while assessing the potential risk of injury. RESULTS: Significant difference between the right and left side (upper limb) was revealed for Shoulder Mobility Test (U=308.5, P=0.014). Odds Ratio analysis revealed that having previous injury in the last 12 months is the only statistically significant injury risk factor (OR=13.71, P=0.02). CONCLUSIONS: Based on this study we can assume that previous injury history reports are crucial in predicting injuries. FMS™ can help in identifying a typical adaptation in throwing shoulder among handball players, but should not be used alone to assess injury risk.